Understanding the Human Dimensions of the Intention to Use Renewable Energy in Hungary Applying an Extended Model of Theory of Planned Behaviour - Szabolcs Nagy; Laszlo Molnar; Noemi Hajdu (Amfiteatru Economic, 2023)
The past year has brought drastic changes to the European energy market. With recent dramatic increases in energy prices, it is of the utmost importance that residential users significantly increase their use of renewable energy. The aim of our study is to understand the complex psychological background of the intention to use renewable energy by applying the Theory of Planned Behaviour (TPB). We extended the original TPB to include environmental concerns. To collect data, an online survey was conducted in Hungary in November 2022. Structural equation modelling (SEM) was used to analyse data from 400 residential users. The resulting model suggests that subjective norms have the greatest direct influence on intention to use renewable energy; however, attitudes formed by environmental concerns are also important influencing factors. Therefore, campaigns to promote the use of renewable energy should focus on the social acceptance of this behaviour and educate target groups about the connection between the energy problem and the challenges of climate change.
Keywords: D12; D91; Q40; Q50; 330; renewable energy use; theory of planned behaviour; attitudes; behavioural intention; Hungary